2014
DOI: 10.4236/ijcm.2014.521179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Nutrition and Dietary Habits on Preeclampsia: A Case-Control Study

Abstract: Introduction: Preeclampsia is one of the most commonly encountered hypertensive disorders of pregnancy that accounts for 20% -80% of maternal mortality in developing countries, including Ethiopia. For many years diet has been suggested to play a role in preeclampsia. However, the hypotheses have been diverse and often revealed inconsistent results across studies. Moreover, rarely were these hypotheses studied in Ethiopia. Therefore, this study aimed to explore whether the incidence of preeclampsia was related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 40 publications
5
29
1
2
Order By: Relevance
“…Researchers have also found a correlation between increased vitamin C, fruit, and vegetable consumption and decreased occurrence of small for gestational age newborns (Rao et al, 2001; Mikkelsen, Osler, Orozova-Bekkevold, Knudsen, & Olsen, 2006; Jain, Wise, Yanamandra, Dhanireddy, & Bocchini, 2007; Ramon et al, 2009). Endeshaw and colleagues (2014) also found increased vegetable and fruit consumption to be protective against preeclampsia. Many women do not adequately eat fruits and vegetables despite the known benefits (Crozier et al, 2009; Krebs-Smith, Guenther, Subar, Kirkpatrick, & Dodd, 2010; Stallings, Gazmararian, Goodman, & Kleinbaum, 2015).…”
Section: Literature Reviewmentioning
confidence: 91%
See 2 more Smart Citations
“…Researchers have also found a correlation between increased vitamin C, fruit, and vegetable consumption and decreased occurrence of small for gestational age newborns (Rao et al, 2001; Mikkelsen, Osler, Orozova-Bekkevold, Knudsen, & Olsen, 2006; Jain, Wise, Yanamandra, Dhanireddy, & Bocchini, 2007; Ramon et al, 2009). Endeshaw and colleagues (2014) also found increased vegetable and fruit consumption to be protective against preeclampsia. Many women do not adequately eat fruits and vegetables despite the known benefits (Crozier et al, 2009; Krebs-Smith, Guenther, Subar, Kirkpatrick, & Dodd, 2010; Stallings, Gazmararian, Goodman, & Kleinbaum, 2015).…”
Section: Literature Reviewmentioning
confidence: 91%
“…Currently, it is recommended that pregnant women obtain 1200–2500 mg/d of calcium and 600–1000 μg/d of folate (Institute of Medicine, 2005). Calcium supplementation and appropriate folate intake have protective effects against preeclampsia (Hofmeyr, Lawrie, Atallah, Duley, & Torloni, 2014; Endeshaw, Ambaw, Aragaw, & Ayalew, 2014). Previous research findings have linked the consumption of certain micronutrients to positive health outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…(19) However, the results of our study differed from those of one study on pregnant or post partum women in Semarang and another study on pregnant women in Makassar, with and without pre-eclampsia, where it was found that low protein intake was a risk factor of preeclampsia in pregnancy. (7,20) Similarly, a study that was conducted in one Indian hospital found that low protein intake was a risk factor of preeclampsia. (21) Low protein intake contributes toward oxidative stress that subseaquently causes preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…(6) According to a study conducted by Kartasurya (7) on 200 pregnant/post partum women (50 pre-eclampsia cases and 150 controls), in women with pre-pregnancy body mass index (BMI) scores of >23 kg/m 2 , the risk of pre-eclampsia was four and a half times greater than in women with pre-pregnancy BMI scores of <23 kg/m 2 . Lipids are involved in the generation of free radicals and polyunsaturated fatty acids (PUFA) tend to be oxidized by free radicals and reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%